2005
DOI: 10.1186/1471-2334-5-108
|View full text |Cite
|
Sign up to set email alerts
|

High frequency of Human Cytomegalovirus DNA in the Liver of Infants with Extrahepatic Neonatal Cholestasis

Abstract: Background: Biliary atresia (BA) is the most severe hepatic disorder in newborns and its etiopathogenesis remains unknown. Viral involvement has been proposed, including the human cytomegalovirus (HCMV). The aims of the study were to use the polymerase chain reaction (PCR) to screen the liver tissue of infants with extrahepatic cholestasis for HCMV and to correlate the results with serological antibodies against HCMV and histological findings.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
55
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 49 publications
(59 citation statements)
references
References 32 publications
3
55
1
Order By: Relevance
“…Lurie et al [35] , after studying four fatal cases of NIHC from CMV, described the presence of cytomegalic cells in the liver from two of them. None were detected in the present study or observed in cases of extrahepatic cholestasis (EHC) [36][37][38] . In CMV hepatitis following orthotopic liver transplantation (immunosuppressed patients), demonstration of cytomegalic inclusion bodies in hematoxylin and eosin sections is sufficient for a diagnosis of CMV hepatitis [39] .…”
Section: Discussionmentioning
confidence: 56%
“…Lurie et al [35] , after studying four fatal cases of NIHC from CMV, described the presence of cytomegalic cells in the liver from two of them. None were detected in the present study or observed in cases of extrahepatic cholestasis (EHC) [36][37][38] . In CMV hepatitis following orthotopic liver transplantation (immunosuppressed patients), demonstration of cytomegalic inclusion bodies in hematoxylin and eosin sections is sufficient for a diagnosis of CMV hepatitis [39] .…”
Section: Discussionmentioning
confidence: 56%
“…8,10,18 Although no unequivocal link has been established between BA and CMV infection, there appears to be a fairly strong correlation between the two, as demonstrated by our study. CMV is a slow replicating virus from the herpes family, infecting only as many as 1% of all neonates in developed countries, 9 but demonstrating up to 90% IgG-positivity in developing countries. 19 Only 5 -10% of infected infants have typical CMV inclusion disease with symptoms of hepatosplenomegaly, jaundice and petechiae; a further 5% having subclinical disease.…”
Section: Discussionmentioning
confidence: 99%
“…15 Although there appears to be a correlation between CMV infection and BA, the significance must still be determined due to the small cohorts studied thus far. 4,5,7,[9][10][11]16,17 Human CMV infection is a strong candidate, being cholestatic in its own right. 5,9 It has also been associated with intrahepatic bile duct destruction and ductal paucity, indicating a possible role in the pathogenesis and progression of extrahepatic BA.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations